2018
DOI: 10.1016/j.rmed.2018.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Real-world safety and efficacy of omalizumab in patients with severe allergic asthma: A long-term post-marketing study in Japan

Abstract: This post-marketing study confirmed the clinically meaningful benefits of omalizumab in a majority of patients from Japan, and showed safety and efficacy in a real-life clinical setting to be consistent with previous reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 71 publications
2
43
0
3
Order By: Relevance
“…17,20,22,23 Real-world studies also reported a reduction in the need for oral corticosteroid (OCS) therapy with omalizumab treatment in patients with moderate to severe allergic asthma. [17][18][19][20][21]24,25,27 A systematic review of 24 realworld studies (N=4117) conducted across 32 countries on the short-and long-term effects of omalizumab in the treatment of severe allergic asthma confirms the abovementioned benefits. 28 To date, there is limited real-world evidence on Canadian asthma patients receiving omalizumab.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…17,20,22,23 Real-world studies also reported a reduction in the need for oral corticosteroid (OCS) therapy with omalizumab treatment in patients with moderate to severe allergic asthma. [17][18][19][20][21]24,25,27 A systematic review of 24 realworld studies (N=4117) conducted across 32 countries on the short-and long-term effects of omalizumab in the treatment of severe allergic asthma confirms the abovementioned benefits. 28 To date, there is limited real-world evidence on Canadian asthma patients receiving omalizumab.…”
Section: Introductionmentioning
confidence: 72%
“…The authors also noted that treatment with omalizumab versus placebo improved asthma symptom scores and quality of life in both steroid-stable and steroid-reduction phases. 2 The results of real-world studies conducted in patients with moderate to severe allergic asthma in Canada, 17 Japan, 18 Israel, 19 and Europe [20][21][22][23][24][25][26][27] corroborate the favorable findings of clinical trials and confirm the effectiveness of omalizumab in reducing exacerbations, 17,18,20,[22][23][24][25][26][27] emergency room visits, 19,23 hospitalizations 24 and improving asthma symptoms and control, 17,22,23,25,26 and quality of life. 17,20,22,23 Real-world studies also reported a reduction in the need for oral corticosteroid (OCS) therapy with omalizumab treatment in patients with moderate to severe allergic asthma.…”
Section: Introductionmentioning
confidence: 80%
“…However, the population demographics of that study differed with respect to age and gender: elevated mean age (59.3 years) with 44% of patients aged >65 years, and more female patients (64.5%). 23 A comprehensive look at asthma control (which was out of scope for this analysis) considers reducing symptoms, airflow limitation, and exacerbation risks by optimizing inhaler techniques, trigger avoidance, adherence, perception of disease, and appropriateness of therapy versus need for escalation. 24 In the current study, due to its retrospective design using the secondary database, data on above clinical outcomes (e.g., symptoms, lung function) could not be collected, and therefore step-up in therapy offers a reasonable, though incomplete, surrogate measure for loss of disease control in patients in the non-severe asthma cohort.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize bias, non-significant results reported in the original publication were included in our pooled estimates. Table 1 summarizes the 42 studies stratified by 30 adult-only studies [24,26,27,[30][31][32][33][34][35][36][37][40][41][42][43][44][45][46][47][58][59][60][61][62][63][64][65][66][67][68] (n = 3558) and 12 adult/ adolescent studies [25,38,39,56,57,[69][70][71][72][73][74][75][76][77] (n = 5819). These 42 studies comprised a total of 9377 patients from 35 countries: 25 in Europe (incl.…”
Section: Other Methodological Considerationsmentioning
confidence: 99%